Interhemispheric transfer of visuomotor conditional learning via the anterior corpus callosum of monkeys. - Eacott, M; Gaffan, D (1990)
Two experiments examined interhemispheric transfer of learning across the anterior corpus callosum in monkeys (Macaca fascicularis). The animals learned a series of visuomotor conditional discrimination problems for food reward. Within each problem the animals were first trained using one hand to make the motor responses, and were then required to use the opposite hand in order to test for intermanual transfer of the initial learning. In Exp. 1, a group of animals with surgical section of the entire corpus callosum and anterior commissure showed a complete absence of intermanual transfer of learning. A second group, in which only the anterior commissure and the posterior part of the corpus callosum were sectioned, leaving the anterior corpus callosum intact, showed good intermanual transfer. Thus, intermanual transfer in the second group represented interhemispheric information transfer via the anterior portions of the corpus callosum. However, in Expt. 2, normal intermanual transfer was seen in a group of animals in which the anterior corpus callosum alone had been sectioned. We conclude that the anterior corpus callosum can mediate interhemispheric transfer of visuomotor conditional learning, but is not the only available route for such transfer in the present task.